2022
DOI: 10.1002/adfm.202111234
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Triggered Ferri‐to‐Paramagnetic Transition Accelerates Redox Couple‐Mediated Electrocatalytic Water Oxidation

Abstract: Redox couple oxidation as an initial step of water oxidation may be key for high electricity consumption in the electrochemical oxygen evolution reaction (OER). Here, a heat-induced magnetic transition strategy is reported to speed up the oxidation kinetics of redox couples. The activation energy of Ni 2+ /Ni 3+ redox couple oxidation is sharply decreased by heating the Ni 0.67 Fe 0.33 O x H y catalyst above a Curie temperature (T c ) of 70 °C. In such a strategy, heat instead of electricity drives the spin fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…[33] In the LSV curve, the small peak at ≈1.3 V is corresponding to the redox reaction of Ni 2+ /Ni 3+ . [8] The turnover frequency (TOF) for Co 3 Cu-Ni 2 MNs, which evaluates the intrinsic activity of the catalyst, [34,35] shows a 0.05 s −1 value under an overpotential of 300 mV (Figure 3c), which is better than bimetallic nanosheets and single metal nanosheets. Significantly, the mass activity value of Co The rotating ring disk electrode (RRDE) method confirms that no obvious by-product peroxide is produced for Co 3 Cu-Ni 2 MNs (Figure 3e and Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] In the LSV curve, the small peak at ≈1.3 V is corresponding to the redox reaction of Ni 2+ /Ni 3+ . [8] The turnover frequency (TOF) for Co 3 Cu-Ni 2 MNs, which evaluates the intrinsic activity of the catalyst, [34,35] shows a 0.05 s −1 value under an overpotential of 300 mV (Figure 3c), which is better than bimetallic nanosheets and single metal nanosheets. Significantly, the mass activity value of Co The rotating ring disk electrode (RRDE) method confirms that no obvious by-product peroxide is produced for Co 3 Cu-Ni 2 MNs (Figure 3e and Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] To overcome the kinetic obstacles, a series of efficient electrocatalysts have been explored such as metal nanoparticles, noble metal-based oxides, and metal complexes. [6][7][8][9][10] Benefiting from the synergistic catalytic effect among metals, and abundant active sites, multivariate metalorganic framework (MOF) is an ideal electrocatalytic framework material. [11][12][13][14][15] Moreover, multivariate MOFs can effectively adjust the electronic structure of metal sites and their morphology, DOI: 10.1002/smll.202301473 thereby promoting intrinsic catalytic and conductive activity compared with single metal MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical water splitting is regarded as one of the most promising pathways for yielding hydrogen. [1][2][3][4] However, the hydrogen yield suffers from slow kinetics of the oxygen evolution reaction (OER) owing to the multi-electronic transfer in OER. [5][6][7] Noble metals, such as Ru and Ir, with high intrinsic catalytic activity, are regarded as ideal catalysts for OER.…”
Section: Introductionmentioning
confidence: 99%
“…We have first demonstrated that the heat-induced ferro-paramagnetic transition accelerates Ni 2+ /Ni 3+ redox couple-mediated electrocatalytic water oxidation, suggesting heat-manipulating electronic state is a potential route to reduce the electrochemical OER overpotentials. Here, we further demonstrated that the heat-manipulated electronic states of a catalyst is interface-dependent.…”
mentioning
confidence: 99%
“…That is, an efficient heat-electricity coupling process would be a fact that the heat and electricity act together to change the electronic chemical potential of the system via a given heat-induced physical effect. We have first demonstrated that the heat-induced ferroparamagnetic transition accelerates Ni 2+ /Ni 3+ redox couplemediated electrocatalytic water oxidation, 12 suggesting heatmanipulating electronic state is a potential route to reduce the electrochemical OER overpotentials. Here, we further demonstrated that the heat-manipulated electronic states of a catalyst is interface-dependent.…”
mentioning
confidence: 99%